Quantum Controlled Teleportation of Arbitrary Two-Qubit State via Entangled States - Lei Shi; Kaihang Zhou; Jiahua Wei; Yu Zhu; Qiuli Zhu (Advances in Mathematical Physics)
We put forward an efficient quantum controlled teleportation scheme, in which arbitrary two-qubit state is transmitted from the sender to the remote receiver via two entangled states under the control of the supervisor. In this paper, we use the combination of one two-qubit entangled state and one three-qubit entangled state as quantum channel for achieving the transmission of unknown quantum states. We present the concrete implementation processes of this scheme. Furthermore, we calculate the successful probability and the amount of classical information of our protocol.